A fully floating system for a wave energy converter with direct-driven linear generator. (15th January 2016) - Gao, Yuping; Shao, Shuangquan; Zou, Huiming; Tang, Mingsheng; Xu, Hongbo; Tian, Changqing
Abstract: Wave energy is one of the most promising renewable energy for power generation. This research develops a novel power take-off methodology to surmount the problems associated with mooring, seawater corrosion and access for maintenance in conventional WEC (wave energy converters) with direct-driven linear generators. Its prototype consists of two bodies, the floating body acting as a buoy to extract the wave energy, while the inner body undergoes a forced oscillation, whose relative motion generates the electronic power. Its feasibility is investigated theoretically by coupling the dynamics of the wave, the floating and the inner bodies and the electromagnetic characteristics of the linear generator. As a result, the generator can induce a highly sinusoidal voltage. Furthermore, the performance of the system is investigated in detail under different conditions. The results show that, a resonance has been achieved in the case with the spring constant of 12, 633 N/m, with a maximum power capture ratio of 57%. The performance of the system is shown to be sensitive to the load resistance, the wave height, and the spring constant. Highlights: A fully floating wave energy converter utilizing the relative motion is proposed. The generator is fixed in an enclosed cavity without contact with the seawater. A coupled dynamic and electromagnetic theoretically model has been established. The linear generator in the WEC can induce a nearly sinusoidal voltage. A resonance has been achieved in the WEC with a maximum power capture ratio of 57%.